Effect of Neodymium and Transition Metals Co-doped on Structural, Optical and Magnetic Properties of BiFeO3 Materials - Dao, Viet Thang (H. : ĐHQGHN, 2017)
Structural, optical and magnetic properties of BiFeO3 and Bi0.9Nd0.1Fe0.95TM0.05O3 (TM = Ni, Co) polycrystallines prepared by sol–gel method have been investigated. X-ray diffraction (XRD) patterns reveal that all samples crystalize in rhombohedrally distorted perovskite structure belonging to R3C space group. The analysis results of both XRD and Raman scattering show the increase of lattice distortion with the co-replacing of Nd and TM ions into A and B sites respectively. All samples exhibit a weak ferromagnetic behavior at room temperature with the enhancement of the magnetization in Nd and TM co-doped samples.